Word Order of Noun and Verb Phrases in Contemporary Persian and English Poems (JOURNAL OF ADVANCES IN LINGUISTICS, 2017)
Literature is a system of semantic markers which convey emotions as well. Sentences in literary texts, particularly poetic ones, are not merely a medium to convey a message. In literary language, there is not a one to one correspondence between words and their meaning. That is in literary texts, the words and consequently sentences do not have their common dictionary meaning. Rather, in many cases, they include the writers or poets intended meaning. For writers and poets, words are not simply means of conveying a message, but a scheme to create beauty and novel innovations. The poets to make more impression on their addressees usually create uncommon sentences in the language. To express their feelings and thoughts, they invert the poems internal word order or sort out the structural system of their poetic sentences counter to standard language. By creating marked words or sentences, they actually seek to communicate their audience artistically and innovatively. Sentence is the poets main instrument that according to traditional grammars definition consists of two parts: subject and predicate. However, in modern linguistics sentence is a set of noun and verb phrases that are joined together as a harmonious whole. Each of noun or verb phrases has a unique structure so that their internal order cannot be changed; however, poets make their utterance poetic by inverting these groups to create greater influence. By using content analysis method, an attempt is made in this article to analyze the internal orders of noun and verb phrases in contemporary poems. The author gratefully acknowledge the financial and other support of this research, provided by the Islamic Azad University. eslamshahr Branch, Tehran ,Iran